1980
DOI: 10.1007/bf00848564
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and reversion of chondrogenesis by retinoic acid in rat limb bud cell cultures

Abstract: Mesenchyme cells derived from embryonic rat limb buds cultured at high density differentiated into chondrocytes. The degree of chondrogenesis was assessed by alcian blue staining, a stain specific for cartilage matrix. The addition of retinoic acid on day 1 of culture inhibited chondrogenesis in a dose-dependent fashion. When retinoic acid was added to the cultures on day 5, the cartilage nodules, consisting of newly differentiated cartilage cells, disappeared during the following 6 days. Coinciding with this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Inhibitory effects of retinoids on cell differentiation, particularly in the process of chondrogenesis, are often cited as the mechanisms by which limb defects are produced in treated embryos. In fact, inhibition of chondrogenesis is readily observed when limb bud mesenchymal cells are exposed to small quantities of retinoids in organ or cell cultures [44][45][46][47]. Both all-trans and 13-cis retinoic acids suppress chondrogenesis in kitro although, as expected, the former is more effective than the latter (Kochhar, unpublished observations).…”
Section: Discussionmentioning
confidence: 64%
“…Inhibitory effects of retinoids on cell differentiation, particularly in the process of chondrogenesis, are often cited as the mechanisms by which limb defects are produced in treated embryos. In fact, inhibition of chondrogenesis is readily observed when limb bud mesenchymal cells are exposed to small quantities of retinoids in organ or cell cultures [44][45][46][47]. Both all-trans and 13-cis retinoic acids suppress chondrogenesis in kitro although, as expected, the former is more effective than the latter (Kochhar, unpublished observations).…”
Section: Discussionmentioning
confidence: 64%
“…When added to limb bud cultures after cartilage nodules have formed, RA induces resorption of cartilage matrix. This effect on differentiated limb bud cells is suppressed by actinomycin D and cyclohexamide, indicating that RA-induced resorption in this system requires RNA and protein synthesis (Gallandre and Kistler, 1980). This resorptive effect on cartilage is also seen when RA is given directly to fetal rat bones in culture (Kistler, 1982).…”
Section: Retinoic Acid Effects On Chondrogenesis and Cartilagementioning
confidence: 83%
“…As previously mentioned, mesenchyme cells isolated from a developing limb will spontaneously undergo chondrogenesis, forming discrete cartilage nodules when plated at high density in micromass cultures (Ahrens et al, 1977(Ahrens et al, , 1979. Alcian blue, a stain specific for glycosaminoglycans (GAGs) in cartilage matrix, has been used to demonstrate that in chick, mouse, and rat limb bud cultures, fewer nodules form in response to RA and those that do form are smaller when compared to nodules in untreated cultures (Gallandre and Kistler, 1980;Hassell et al, 1978;Hassell and Horigan, 1982;Lewis et al, 1978;Zimmerman and Tsambos, 1985). The inhibitory effects of RA on chondrogenesis are dose-dependent and irreversible.…”
Section: Retinoic Acid Effects On Chondrogenesis and Cartilagementioning
confidence: 98%
“…Saxena and Niazi (1977) also observed excessive dedifferentiation in retinoid-treated regenerating hindlimbs of toad tadpoles, and retinoid-induced resorption of 6-7 day chick embryo limb cartilages and fetal rat humeri in vitro has been reported (Fell and MeUanby 1952;Kistler 1978). Kistler (1978) and Gallandre and Kistler (1980) have shown that RA-induced resorption of fetal rat cartilage requires de novo synthesis of RNA and protein, since resorption can be inhibited in the presence of RA by inhibitors of RNA and protein synthesis such as actinomycin D and cyclohexamide. Whether RNA and protein synthesis are required in regenerating limbs for normal dedifferentiation or for the excessive dedifferentiation evoked by RA is not known.…”
Section: Effects Of Ra On Normal and Double Anterior Regeneratesmentioning
confidence: 83%